Pengaruh Pelaksanaan Kegiatan TPK (Tim Pendamping Keluarga) Terhadap Sikap dan Perilaku Pencegahan Stunting pada Keluarga Balita Berisiko Stunting di Kecamatan Dungkek Kabupaten Sumenep - Fendi, Yuskinau; Wahyuningsih, Atik Setiawan; Kusumawati, Prima Dewi (Lembaga Teewan Journal Solutions, 2026)
Stunting remains a major public health problem in Indonesia affecting the quality of human resources. Although the Family Assistance Team (TPK) has actively implemented assistance programs in Dungkek District, stunting cases continue to fluctuate. This study examined the effect of TPK implementation on attitudes and stunting prevention behaviors among families with under five children at risk of stunting. This quantitative cross-sectional study included 148 families with under-five children at risk of stunting selected by proportional random sampling. Data were collected using a structured questionnaire and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 4. TPK implementation had a positive and significant effect on stunting prevention behavior (β = 0.139; t = 2.171; p = 0.030) and stunting prevention attitude (β = 0.629; t = 12.944; p < 0.001). Attitude also positively affected stunting prevention behavior (β = 0.720; t = 10.603; p < 0.001) and significantly mediated the relationship between TPK implementation and behavior (β = 0.453; t = 8.374; p < 0.001). TPK implementation improved family attitudes, which subsequently promoted better stunting prevention behaviors. The indirect effect through attitude exceeded the direct effect, indicating that attitude is a key mediating variable. Strengthening TPK through health education, nutrition counseling, growth monitoring, and continuous family assistance is expected to promote sustainable stunting prevention behaviors and accelerate stunting reduction in Dungkek District.